CCR10: a comprehensive review of its function, phylogeny, role in immune cell trafficking and disease pathogenesis - Willuveit, Amanda Lopes; Stefanini, Ana Carolina Buzzo; Matozo, Taís; Marti, Luciana Cavalheiro (Frontiers in Immunology, 2025)
CCR10, the latest classified receptor in the CC chemokine family, plays a critical role in tissue-specific immune responses, particularly in skin and mucosal immunity. By interacting with its ligands, CCL27 and CCL28, it regulates immune cell trafficking, contributing to homeostasis, wound healing, and mucosal defense. However, CCR10 has also been implicated in inflammatory disorders, autoimmune diseases, and cancer progression, where it may facilitate immune evasion and metastasis. Despite its dual roles, CCR10 represents a promising therapeutic target, potential applications in modulating immune responses for inflammatory diseases and oncology. A deeper understanding of its mechanisms and interactions could provide valuable insights into immune system regulation, disease progression and clinical relevance. This review explores CCR10’s molecular structure, biological functions, and potential for therapeutic intervention.